2008
DOI: 10.2176/nmc.48.546
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Seizure Outcome in Patients Undergoing Resection of Lesions Detected by Magnetic Resonance Imaging

Abstract: The long-term efficacy of resective surgery was investigated in patients with lesions detected by magnetic resonance (MR) imaging. Thirty of 47 patients who had undergone lesionectomy between 1987-2001 were followed up by questionnaire. Patients with extratemporal resections outnumbered those with temporal lobe resections. The mean follow-up period was 12.4 ± 3.7 years. Outcomes were graded according to Engel's criteria, and an arbitrary seizure outcome score was given for quantitative assessment. The mean sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Apart from this subgroup, the success rate for remaining patients, as evidenced by complete abolition of seizures, was considerably diminished. These low rates of seizure‐freedom stood in stark contrast to surgical outcome for seizures caused by other pathologic substrates including hippocampal sclerosis, porencephaly, vascular malformations, and tumors (Zentner et al., 1997; Jeong et al., 1999; Moritake et al., 2008).…”
mentioning
confidence: 97%
“…Apart from this subgroup, the success rate for remaining patients, as evidenced by complete abolition of seizures, was considerably diminished. These low rates of seizure‐freedom stood in stark contrast to surgical outcome for seizures caused by other pathologic substrates including hippocampal sclerosis, porencephaly, vascular malformations, and tumors (Zentner et al., 1997; Jeong et al., 1999; Moritake et al., 2008).…”
mentioning
confidence: 97%
“…13) Patients free of seizures and those with at least 90% reduction in seizure frequency reported significant improvements in HRQOL at 24 months. 15) Our previous study 17) on the long-term seizure outcome in the same subjects indicated that lesionectomy based on MR imaging in patients of intractable epilepsy was effective for long-term seizure control and the postoperative seizure outcome was related mainly to the pathology of the epileptogenic lesions, with excellent seizure outcome in patients in the Non-CD exT group and poor in those in the CD exT group. The present study of long-term QOL outcome showed compatible findings.…”
Section: Discussionmentioning
confidence: 94%
“…The histological diagnoses of the epileptogenic lesions were shown previously. 17) The most prominent findings were neuronal loss and gliosis, which was associated with cerebral scarring or porencephaly after head injury, infection, or vascular malformation, or was of unknown origin. Mesial temporal sclerosis was found in 6 patients, and cortical dysplasia and cryptic angioma in 3 patients each.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations